ADTU-04 Faecal calprotectin in PSC-IBD: a novel marker of cholangitis. (8th June 2018) - Pavlidis, Polychronis; El-Sherif, Yasser; Warner, Ben; Gulati, Shraddha; Sarras, Konstantinos; Alberts, Ellie; Segal, Joe; Rashid, Tamir; Harrison, Phil; Devlin, John; Heneghan, Michael; Fueyo, Alberto; et al.
Abstract : Introduction: Primary sclerosing cholangitis (PSC) is a chronic inflammatory condition of the bile ducts leading to fibrosis and end stage liver disease. A lack of robust non-invasive biomarkers has been hindering disease monitoring and development of optimal therapies. We have previously noted that the high levels of faecal calprotectin (fcal) seen in PSC-IBD patients belie the mild or quiescent intestinal inflammation. An unsupervised proteomics study identified biliary calprotectin as a potential biomarker. Here, we test the hypothesis that fcal is a marker of biliary injury in PSC. Methods: We analysed paired endoscopic activity data (UCEIS) and fcal results of patients with PSC-IBD (n=20) or UC (n=20) who underwent colitis surveillance in the context of a colitis surveillance pilot study. Relevant clinical data was recorded prospectively. Recruiting consecutive patients attending for ERCP (n=6) allowed for the concomitant testing of biliary and faecal calprotectin. Results: As expected, fcal strongly correlated with severity of mucosal injury (UCEIS) in UC [r=0.82, 95% CI(0.58, 0.92), p<0.0001]. However, the correlation was weaker in PSC-IBD [r=0.59, 95% CI(0.19, 0.82), p=0.006]. Moreover, in patients with PSC-IBD and quiescent colitis (UCEIS: 0–1) fcal concentration was significantly higher in comparison to UC patients with comparable endoscopic activity [279 ug/g (10, 1560) vs. 30 (10, 161), p=0.015)]. A trend towards abnormal liver biochemistry was seen in those PSC-IBD with higher fcal [ALP: 250IU/L (113, 561) vs. 83 (59, 170), p=0.06, GGT: 351 U/L (117, 1014) vs. 51 (29, 153) p=0.02, AST: 53 U/L (26, 85) vs. 37 (22, 43), p=ns]. UC patients with quiescent colitis and fcal >150 had a higher risk of colitis relapse in 12 months [HR=7.6, 95% CI(1.8, 33.6)] in comparison to those with fcal <150. However, in patients with PSC-IBD and quiescent colitis a fcal >150 was associated instead with a higher risk of cholangitis associated complications (need for antibiotics or stent insertion), HR=6.5, 95% CI(1.3, 33.9). Strikingly, biliary calprotectin concentration showed a strong correlation with fcal concentration (r=0.90, p=0.04). Interestingly, immunostaining of biliary brushings for calprotectin demonstrated positive staining in cholangiocytes as well as neutrophils and macrophages. Conclusion: In patients with PSC-IBD and quiescent colitis the identification of a raised fcal is likely to herald complications of inflammation in the bile ducts rather than the colon. In this setting, fcal may be a valuable prognostic biomarker of cholangitis. Additionally, our data suggest that in PSC, the source of raised fcal may also be the damaged biliary epithelium.